If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 10 = -74 + -9x Reorder the terms: 10 + 3x = -74 + -9x Solving 10 + 3x = -74 + -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. 10 + 3x + 9x = -74 + -9x + 9x Combine like terms: 3x + 9x = 12x 10 + 12x = -74 + -9x + 9x Combine like terms: -9x + 9x = 0 10 + 12x = -74 + 0 10 + 12x = -74 Add '-10' to each side of the equation. 10 + -10 + 12x = -74 + -10 Combine like terms: 10 + -10 = 0 0 + 12x = -74 + -10 12x = -74 + -10 Combine like terms: -74 + -10 = -84 12x = -84 Divide each side by '12'. x = -7 Simplifying x = -7
| 98-2x=5x+7 | | -28-2=7-9x | | 3x+5x+x= | | 6x+40=13x-23 | | (11s+r)(-7r+s)= | | (X^2+1)(X+9)= | | 5x-29=31 | | (100+X)(X-100)= | | (x+y)(z+y)= | | (x+5)(y+10)= | | 72-7j=72 | | (x-6)(x+9)= | | 6x-5y=8 | | (m^2-7m-6)(7m^2-3m-7)= | | 4-5x=9x+18 | | 3-x=9-3x | | 14-6b=4b+34 | | 9-3s=4s+30 | | 135-5x=31x+23 | | 13-4y=2y-11 | | -2b+7-3n=2 | | 14x-10=166-38x | | (3x+5)(4x-1)= | | 2(x-5)-6(3x-1)+8=2(2x-8)-(3x+4-3) | | 7x-2=14+3x | | 7x+9-3x+2=5 | | 12x-5=8x+31 | | 500*1/2+70= | | 6x+10=2x+4 | | 8+4x=10x+6 | | x^2-60x+720=0 | | 8x+4=10x+6 |